Phenotypic and potential virulence features of Salmonella enterica serotypes from cancer patients in Kolkata, India - Goutam Chowdhury; Sanjay Bhattacharya; Gaurav Goel; Soumyadip Chatterji; Kei Kitahara; Ayumu Ohno; Melissa Glenda Lewis; Shin-ichi Miyoshi; Thandavarayan Ramamurthy; Asish K. Mukhopadhyay (BMC Infectious Diseases, 2025)
Abstract Background Salmonella enterica is a leading cause of gastroenteritis and enteric fever. In this study, we sought to investigate the phenotypic and genotypic characteristics of S. enterica isolated from the cancer patients admitted at the Tata Medical Center, Kolkata over a period of eight years (2016–2023). Methods Salmonella enterica isolates were identified by standard biochemical and serotyping. Antimicrobial susceptibility was tested by disk diffusion method and virulence genes were identified by PCR. The genetic relatedness of strains was determined by pulsed-field gel electrophoresis (PFGE) methods. Results A total of 122 S. enterica isolates were identified and classified into 18 different serovars. S. Typhimurium (28.7%), S. Kentucky (22.1%), S. Enteritidis (13.9%), S. Typhi (5.7%) and S. Agona (5.7%) were identified as the common serovars. S. enterica infection was more often detected in adults (77.9%) than in children of 6–18 years old (11.4%) and < 5 years of age (10.6%). The maximum number of S. enterica was isolated from blood (52.4%) followed by those isolated from stool (36.9%) and urine (5.7%). S. enterica infections were detected among patients with chronic myelogenous leukemia (CML)/acute lymphoblastic leukemia (ALL) (24.6%) than Hodgkin lymphoma/non-Hodgkin lymphoma (16.4%), multiple myeloma (9.8%), lung adenocarcinoma (9%), prostate adenocarcinoma (6.6%), and endometrium carcinoma (5.7%). S. Kentucky showed a statistically significant association with hematologic malignancies (p < 0.001), whereas S. Enteritidis was significantly present in Hodgkin lymphoma and acute lymphoblastic leukemia/Chronic myelogenous leukemia cancer types (p = 0.004). Most of the S. enterica isolates displayed resistance to erythromycin (62.9%), nalidixic acid (62.9%) and tetracycline (33.9%). Salmonella pathogenicity island (SPI)-associated genes (orgA, ssaQ, misL, invE/A, spi4D, pipA and ttrc) were uniformly present in majority of the isolates. The hyper invasive locus (hilA), Salmonella enterotoxin (stn), Salmonella outer protein (sopB), virulence plasmid (spvC), and plasmid encoded fimbriae (pefA) genes were present in 76%, 69%, 51%, 32% and 17% of the isolates, respectively. Clonal analysis of the representative homologous serovars using pulsed-field gel electrophoresis revealed specific clusters with 40 to 90% similarity within each serotype. Conclusions Cancer patients are at increased risk of morbidity due to secondary infections, like S. enterica. Continuous monitoring of antimicrobial resistance patterns and virulence gene profiles in S. enterica isolates from this vulnerable group is critical to guide clinical management and treatment strategies.